Early effects of PCE exposure on visual function among dry cleaning workers - Chiesi, Andrea; Gioia, Tiziana Concetta; Modenese, Alberto; Abbacchini, Carlotta; Borsari, Lucia; Clò, Emanuele; Di Rico, Renato; Ferrari, Davide; Gobba, Fabrizio Maria (La Medicina del Lavoro, 2016)
Background: A number of studies have shown a possible correlation between exposure to perchlorethylene (PCE) in dry cleaning workers and impairment of colour perception. Objectives: to ascertain the possible presence of alterations in visual function in a group of workers exposed to current limit value levels of PCE. Methods: The study was conducted on 38 workers exposed to PCE in 21 dry cleaning establishments in the district of Modena and 60 controls selected according to criteria of comparability. We measured exposure to PCE among the dry cleaning workers using environmental monitoring (mean exposure 16.9 mg/m3). Both groups then answered a medical history questionnaire and underwent the Ishihara test for evaluating exclusion criteria followed by Lanthony D15d and Visual Acuity in Contrast Reduced (VCS) tests to evaluate changes in visual function. The results of Lanthony’s test were expressed using Index Confusion Chromatic (ICC). Results: In the cases the average value of ICC was 1.28 (DS 0.21) and in the controls 1.15 (SD 0.21); the difference was statistically significant (p